Reinventing Cultural Identities in Diaspora: A Mother-Daughter Dyad in Tan’s Narratives - Bhandari, Nagendra Bahadur (Tribhuvan University Journal, 2018)
Immigrants suffer problematic cultural identities due to their bicultural allegiances to their host and native cultures. They can not be totally free from their ‘being’, the shared cultural and historical experiences. As a result, they follow their cultural practices of native country even in their diasporic existences. At the same time, they adopt and follow the cultural practices of the host country. In fact, they are living in the cultural third space simultaneously oscillating between two cultures. In such cultural in-between’s, the first generation and the second generation immigrants undergo different experience in diaspora. In this article, Chinese American writer Amy Tan’s two fictions namely The Joy Luck Club and The Bonesetter’s Daughter are analyzed focusing on cultural identities of second generation immigrants. The second generation in these narratives is the daughters of Chinese immigrant mothers. Their relationship with their mothers unfolds their simultaneous attraction and distraction to the both native and host culture. Consequently, their cultural identities remain unstable, blurred and in the processes of transformation in the cultural third space of diaspora.